Implementation of Investigations and Investigations in Revealing Criminal Acts of Premeditated Murder - Fahrur Rozi, Agus; Santiago, Faisal; Barthos, Megawati (Jurnal Indonesia Sosial Sains, 2023)
Efforts to investigate and investigate the crime of premeditated murder is regulated in the Criminal Procedure Code (KUHAP), namely Law Number 8 of 1981, Article 1 points 1 and 2 formulate the meaning of investigation. The reality on the ground shows that the implementation of investigations and investigations in uncovering cases of premeditated murder cannot be carried out optimally because there are obstacles to the lack of witnesses and evidence. The formulation of the problem in this study is: How is the implementation of investigations and investigations in uncovering cases of premeditated murder? The author uses an empirical juridical approach, using primary and secondary data. Data analysis using qualitative analysis. The results show that: The examination cycle should be done expertly by agents in view of regulation other than the Criminal Methodology Code which frames the legitimate reason for specialists is Police Guideline (Perpol) Number 6 of 2019 concerning the Nullification of Perkap Number 14 of 2012 concerning The executives of Criminal Examination.